Loss to Follow-up and Unplanned Readmission After Emergent Surgery for Acute Subdural Hematoma. Issue 3 (13th September 2022) - Guidry, Bradley S.; Tang, Alan R.; Thomas, Harrison; Thakkar, Rut; Sermarini, Anthony; Dambrino, Robert J.; Yengo-Kahn, Aaron; Chambless, Lola B.; Morone, Peter; Chotai, Silky
Abstract : BACKGROUND: Loss to follow-up (LTF) and unplanned readmission are barriers to recovery after acute subdural hematoma evacuation. The variables associated with these postdischarge events are not fully understood. OBJECTIVE: To determine factors associated with LTF and unplanned readmission, emphasizing socioeconomic status (SES). METHODS: A retrospective analysis was conducted of surgical patients with acute subdural hematoma managed operatively from 2009 to 2019 at a level 1 regional trauma center. Area Deprivation Index (ADI), which is a neighborhood-level composite socioeconomic score, was used to measure SES. Higher ADI corresponds to lower SES. To decrease the number of covariates in the model, principal components (PCs) analysis was used. Multivariable logistic regression analyses of PCs were performed for LTF and unplanned readmission. RESULTS: A total of 172 patients were included in this study. Thirty-six patients (21%) were LTF, and 49 (28%) patients were readmitted; 11 (6%) patients were both LTF and readmitted ( P = .9). The median time to readmission was 10 days (Q1: 4.5, Q3: 35). In multivariable logistic regression analyses for LTF, increased ADI and distance to hospital through PC2 (odds ratio [OR] 1.49; P = .009) and uninsured/Medicaid status and increased length of stay through PC4 (OR 1.73; P = .015) significantly contributed to the risk of LTF. Unfavorable discharge functional status and nonhome disposition through PC3 were associated with decreased odds of unplanned readmission (OR = 0.69; P = .028). CONCLUSION: Patients at high risk for LTF and unplanned readmissions, as identified in this study, may benefit from targeted resources individualized to their needs to address barrier to follow-up and to ensure continuity of care.